Efektivitas Kahoot dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran PAI di SMA Islam Nurul Ihsan Palangka Raya - Sidqi, Ansori; Kinasih, Anya Dani; Norhidayah, Norhidayah; Jasiah, Jasiah (FONDATIA, 2025)
In today's digital era, the integration of technology into Islamic Religious Education (PAI) instruction has become essential to enhance effectiveness and student interest, particularly as learners tend to become disengaged with conventional methods. This study aims to examine the effectiveness of using the interactive learning platform Kahoot in improving student learning outcomes in PAI at SMA Islam Nurul Ihsan Palangka Raya. The research method employed was quantitative with a one-group pretest-posttest design involving 15 eleventh-grade social science students as subjects. Data were collected through learning outcome tests administered before and after the treatment and analyzed using the Shapiro-Wilk normality test and paired sample t-test with the help of SPSS 25. The results showed a statistically significant improvement in learning scores (p = 0.457 > 0.05) after the use of Kahoot, indicating its effectiveness in enhancing motivation, engagement, and understanding of PAI material through an interactive, enjoyable, and competitive learning environment. The conclusion of this study is that digital tools like Kahoot are effective strategies for improving the quality of PAI instruction. The implications of these findings suggest that teachers and educational institutions should adopt innovative, technology-integrated teaching methods to address the challenges of modern education.